Why neotropical primatologists should read Opossums - Lynch, Jessica W. (Neotropical Primates, 2021)
Book Review of: Robert S. Voss and Sharon A. Jansa (2021) Opossums: An Adaptive Radiation of New World Marsupials. Johns Hopkins University Press, Baltimore. 313 pp. ISBN: 9781421439785 (hardcover), 9781421439792 (ebook). <https://jhupbooks.press.jhu.edu/title/opossums>